Accurate Approach in the Treatment of Oral Bisphosphonate-Related Jaw Osteonecrosis - Faloni, Ana Paula de Souza [UNESP]; Queiroz, Thallita Pereira; Comelli Lia, Raphael Carlos; Cerri, Paulo Sérgio [UNESP]; Margonar, Rogerio; Rastelli, Alessandra Nara de Souza [UNESP]; Marcantonio, Elcio (Lippincott Williams & Wilkins, 2011)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is not completely understood and difficult to treat. Even though the occurrence of BRONJ is mainly related to the therapy with intravenous bisphosphonates (BPs), this article reports a case of long-term oral BP use and BRONJ occurrence. In addition, a literature review provides some additional information about BPs, BRONJ, and also a guideline for the prevention and treatment of BRONJ stages. A 79-year-old patient presented intense and persistent pain, purulent secretion, and exposed bone at the right side of the lower jaw. Thus, she was submitted to anamnesis, radiologic and tomographic examinations, and bacterial culture and sensitivity tests. These procedures were followed by surgical debridement of the bone and surrounding tissues/cyst and antibiotic prescription and histopathologic analysis of the fragments. Together, the examinations performed showed the occurrence of stage 2 BRONJ. Moreover, the antibiotic prescription, discontinuation of oral BP, and surgical procedures ensure that the patient had no more symptoms. Therefore, considering the presented case, we believe that an accurate approach is promising to diagnose and treat stage 2 BRONJ and other associated pathologic findings.
Keywords: Sodium alendronate; osteonecrosis; cyst; lower jaw; treatment